Enzymatic racemization of alcohols and amines: An approach for bi‐enzymatic dynamic kinetic resolution. Issue 2 (22nd November 2019) - Musa, Musa M.
Abstract: Racemization is the key step to turn a kinetic resolution (KR), which suffers from the well‐known drawback of being limited to a maximum yield of 50% with high enantiopurity, into a dynamic kinetic resolution (DKR) process. Enzyme‐based racemization of enantiopure alcohols and amines has gained significant interest in recent years. This review covers recent advances in enzyme‐based racemization approaches and their potential applications in bi‐enzymatic DKR. Abstract :